Hyper-order baryon number fluctuations at finite temperature and density - Fu, Wei-jie; Luo, Xiaofeng; Pawlowski, Jan M.; Rennecke, Fabian; Wen, Rui; Yin, Shi (Physical review, 2021)
Fluctuations of conserved charges are sensitive to the QCD phase transition and a possible critical end point in the phase diagram at finite density. In this work, we compute the baryon number fluctuations up to tenth order at finite temperature and density. This is done in a QCD-assisted effective theory that accurately captures the quantum- and in-medium effects of QCD at low energies. A direct computation at finite density allows us to assess the applicability of expansions around vanishing density. By using different freeze-out scenarios in heavy-ion collisions, we translate these results into baryon number fluctuations as a function of collision energy. We show that a nonmonotonic energy dependence of baryon number fluctuations can arise in the noncritical crossover region of the phase diagram. Our results compare well with recent experimental measurements of the kurtosis and the sixth-order cumulant of the net-proton distribution from the STAR Collaboration. They indicate that the experimentally observed nonmonotonic energy dependence of fourth-order net-proton fluctuations is highly nontrivial. It could be an experimental signature of an increasingly sharp chiral crossover and may indicate a QCD critical point. The physics implications and necessary upgrades of our analysis are discussed in detail.
Gesehen am 19.01.2022